UPAYA ORGANISASI AISYIYAH DI GORONTALO UNTUK MENCAPAI TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGs) - Moon Hidayati Otoluwa (LP2M Universitas Bina Mandiri Gorontalo, 2018)
ABSTRACT : Sustainable Development Goals (SDGs) which is acknowledged in 2015 is a continuity of Millennium Development Goals (MDGs). It becomes a new history in global development as the agreements of SDGs in the 70th general assembly held by United Nations have aims in universal development and start in 2016 up to 2030. According to Panuluh (2016) SDGs bring up five basic principles which are balancing among economic, social, and environment. They are (1) People, (2) Planet (3) Prosperity (4) Peace, and (5) Partnership. They have 17 aims and 169 targets. Aisyiyah is a women movement and born from Muhammadiyah organization which concern their programs in education, health, economic. Most of their programs are as a reflection of movements for gender equality. Islam is a religion that glorifies women. It is mentioned a lot in the Qur'an, but there are some habits that make them appear to be inferior to men. These habits position their activities only about taking care of the household. Since the establishment of Aisyiyah, the dignity of women began to raise especially Muslim women. Aisyiyah raised the level of women through education and organization. This makes women dare to appear in public and many play an important role in various aspects of life. In other words, this organization supports the target of SDGs in point 3 (good health and well-being), 4 (quality education), 5 (gender equality), and 8 (decent work and economic growth). Based on the background above, it becomes important to conduct research on the efforts of Aisyiyah in educating women in Gorontalo. The purpose of this research was to describe the efforts of Aisyiyah in education, health, and economic field which support SDGs. The significance of this research is to enrich the knowledge of the efforts of Aisyiyah in education, health, and economic field. It also provides input as contribution and thought for the development of education, health, and economic aspects in Gorontalo in order to achieve SDGs. The data are collected through documentation and interview. The data are analyzed qualitatively. The result shows that the efforts of Aisyiyah in education are reflected through its development of formal schools from kindergarten up to university level. The schools spread out in the city and five districts of Gorontalo province, while the university is located only in Gorontalo district. Aisyiyah has role in running several activities as health program. There are mother and children hospitals and health centers of Aisyiyah. Socialization about the danger of drugs and free sex are regularly done in schools. In economic filed, Aisyiyah develops several business charity in form of home industry, training of life skills, and BUEKA